3D‐Printable Fluoropolymer Gas Diffusion Layers for CO2 Electroreduction. Issue 7 (14th January 2021) - Wicks, Joshua; Jue, Melinda L.; Beck, Victor A.; Oakdale, James S.; Dudukovic, Nikola A.; Clemens, Auston L.; Liang, Siwei; Ellis, Megan E.; Lee, Geonhui; Baker, Sarah E.; Duoss, Eric B.; Sargent, Edward H.
Abstract: The electrosynthesis of value‐added multicarbon products from CO2 is a promising strategy to shift chemical production away from fossil fuels. Particularly important is the rational design of gas diffusion electrode (GDE) assemblies to react selectively, at scale, and at high rates. However, the understanding of the gas diffusion layer (GDL) in these assemblies is limited for the CO2 reduction reaction (CO2 RR): particularly important, but incompletely understood, is how the GDL modulates product distributions of catalysts operating in high current density regimes > 300 mA cm −2 . Here, 3D‐printable fluoropolymer GDLs with tunable microporosity and structure are reported and probe the effects of permeance, microstructural porosity, macrostructure, and surface morphology. Under a given choice of applied electrochemical potential and electrolyte, a 100× increase in the C2 H4 :CO ratio due to GDL surface morphology design over a homogeneously porous equivalent and a 1.8× increase in the C2 H4 partial current density due to a pyramidal macrostructure are observed. These findings offer routes to improve CO2 RR GDEs as a platform for 3D catalyst design. Abstract : Multiscale structural control in 3D‐printable fluoropolymers enables highly tunable gas‐diffusion electrodes. By modulating the diffusion of reactants to and products from the catalyst layer during electroreduction, the product distribution is shifted in favor of higher carbon products. Insights into the rational design of electrodes offer a platform for developing and optimizing next‐generation flow reactors.